Understanding comfort and health of outpatient workers in hospitals, a mixed-methods study - Eijkelenboom, AnneMarie (A+BE | Architecture and the Built Environment, 2021)
Against the backdrop of an increasing need for healthcare, staff shortages and relatively high rates of sick leave, understanding of wellbeing (comfort and health) of hospital workers is important. This research aims to provide a contribution, through a mixed-methods approach, with broad and in-depth insights into comfort and health. Therefore, data have been collected from questionnaires, building inspections, interviews, and photos, and analysed with several techniques. Personal, work, and building-related aspects were included in data collection, because a preliminary literature review identified mutual relations with comfort and health. As previous studies on outpatient workers were missing, while staff is generally less satisfied with comfort than patients, this research focuses on staff in outpatient areas. To gain insights into the outpatient workers’ comfort and health, four important aspects are highlighted: differences in comfort in relation to room types, occupant profiles differentiated by the individuals’ preferences and satisfaction, changes of preferences due to contextual changes, and associations of health with building-related aspects. This research builds on previous studies which identified indoor environmental quality (IEQ) profiles of home occupants and school children. New are social comfort profiles, comparison between room types and contextual influence on preferences, as well as the studied occupant group and building. The study enables academical and practical exploration of preferences and perceptions of comfort and their integration in the design process. AnneMarie Eijkelenboom, architect with 25 years’ experience, is determined to improve wellbeing of occupants through expansion and integration of academical knowledge and practical experience in design of buildings.